Social Review of Public Perception of PT. BEL's Corporate Social Responsibility (CSR) Policy in Seunagan District - Edi Saputra; Cut Khairani; M. Muhtarom (Manunggal Halim Jaya, 2026)
This study aims to describe the community's perception of the implementation of PT. BEL's Corporate Social Responsibility (CSR) program in Seunagan District, Nagan Raya Regency. This study uses a qualitative method with a phenomenological approach, in which researchers seek to understand the experiences and views of the Ring 1 community regarding the implementation of the company's CSR program. Data were obtained through in-depth interviews with community leaders, village officials, and program beneficiaries. The results of the study indicate that the community has a positive perception of PT. BEL's CSR program because it is considered to provide a real contribution to improving welfare, especially in the fields of education, health, social, and economics. However, the implementation of CSR is considered uneven and unsustainable because it still relies on proposals from the village government and there is a lack of transparency and coordination between the company and the local government. The implementation of PT. BEL's CSR program is also still short-term and does not have clear continuity, so its benefits have not been felt comprehensively by the community. Therefore, improved coordination, strategic planning, and periodic evaluation are needed so that CSR implementation can be more effective, inclusive, and sustainable in supporting the social and economic development of the communities around the company's operational areas.